The GTA project: graduate teaching assistant development and professionalization as emerging disciplinary scholars and composition instructors - Halseth, Madeline, author; Palmquist, Mike, advisor; Doe, Sue R., committee member; Quynn, Kristina, committee member (Colorado State University. Libraries, 2022)
Graduate Teaching Assistants (GTAs) constitute a large portion of the teaching population in Writing Studies and Composition (WSC) programs across the country. Although GTAs have many roles, in WSC they are most often employed as instructors of record in mandatory general education writing courses, including first-year composition courses. While composition GTAs are situated within the English department, they are further positioned as emerging scholars and professionals within a specific disciplinary area under the larger umbrella of English studies, such as creative writing, TEFL/TESL, writing studies, English education, and literature. Consequently, as GTAs progress through their program and develop disciplinary and professional identities, it can be inferred that their pedagogical goals and approaches to the teaching of writing will develop as well. This study builds on research addressing the pedagogical experience and professionalization of GTAs within a context that is shaped by neoliberal values in higher education. This project addresses the two primary questions: (1) How does an English department GTA's disciplinarity and ecologies of influence affect their pedagogical goals and approaches to teaching first-year composition as they progress in their graduate program? (2) How do systems of power within the university impact GTAs' pedagogical goals and approaches to teaching first-year composition and their perception of self-efficacy and empowerment as instructors? To explore these questions, seven composition GTAs participated in a qualitative study that included surveys, interviews, and voice memos. The goal of this study was to map the complex university systems and personal factors that impact composition GTAs' development as disciplinary scholars and composition instructors. Results indicate that as GTAs progress in their disciplinary programs, they begin to approach the teaching of writing from a disciplinary perspective that aligns their disciplinary writing practices with their pedagogical goals and strategies for first-year composition courses. These GTAs are heavily impacted by their disciplinary mentors, cohort, and the complex university systems that they must navigate as they fulfill their roles as graduate students, instructors of record, and emerging disciplinary scholars. WPAs and faculty should consider the critical role of mentoring that GTAs require as they develop into composition instructors in order to support and guide future scholars and instructors in the field of writing studies and composition.
Keywords: composition program; mentorship; writing studies; graduate teaching assistant; activity theory; writing pedagogy education